2022
DOI: 10.1155/2022/3835545
|View full text |Cite|
|
Sign up to set email alerts
|

Transnasal High-Flow Oxygen Therapy versus Noninvasive Positive Pressure Ventilation in the Treatment of COPD with Type II Respiratory Failure: A Meta-Analysis

Abstract: Objective. To compare the safety and efficacy of transnasal high-flow oxygen therapy (HFNT) and noninvasive positive pressure ventilation (NIV) in the treatment of chronic obstructive pulmonary disease (COPD) with type II respiratory failure. Methods. PubMed, the Cochrane Library, Embase, CBM, CNKI, and other databases were searched for randomized controlled trials (RCTS) on the efficacy of HFNT and NIV in the treatment of COPD. Meta-analysis was conducted using RevMan 5.3 software after two researchers screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A higher score indicates a more severe condition and a higher predicted mortality. (3) Complications: Incidence of complications during the treatment period was recorded. Complications included gastric distension, nasal bleeding, aspiration, and facial pressure injuries.…”
Section: Secondary Observation Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher score indicates a more severe condition and a higher predicted mortality. (3) Complications: Incidence of complications during the treatment period was recorded. Complications included gastric distension, nasal bleeding, aspiration, and facial pressure injuries.…”
Section: Secondary Observation Indicatorsmentioning
confidence: 99%
“…Diagnostic criteria for type II respiratory failure include an arterial oxygen partial pressure (PaO 2 ) below 60 mmHg and an arterial carbon dioxide partial pressure (PaCO 2 ) exceeding 50 mmHg. This disease is characterized by a rapid onset, swift progression, and a notably high mortality rate, significantly impacting patient survival [3,4]. Consequently, prompt and efficacious interventions are imperative in the management of type II acute respiratory failure, with the goal of alleviating clinical symptoms and reducing mortality.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by airflow limitation with persistent and progressive dyspnea and is often accompanied by chronic coughing and chest tightness. [1][2] Acute exacerbations of COPD (AECOPD) are more common in middle-aged and older patients, often occur in combination with type II respiratory failure, and are characterized by weak coughing, concomitant infection, and poor lung function, which have negative effects on patient health, and increase the risks of hospitalization, readmission and disease progression. As AECOPD worsens, CO 2 retention and hypercapnic respiratory failure may occur.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%